Bird Species Richness, Density, Diversity and Trees Composition in Government College Kaduna, Kaduna State, Nigeria - Agbo, Boniface Onyeke; Abba, Patience Zitchat (Journal of Science Research and Reviews, 2025)
Man’s interaction with the abiotic and biotic world is an integral part of his existence. We examined ecological indices such as richness, diversity and evenness of bird and tree species as bio-indicators of the health of a defunct military camp now Government College Kaduna in Kaduna, Nigeria. Our survey was carried out in the morning with the objective of evaluating bird species distribution and tree composition within the College. Birds sighted, heard and seen in flight within 25m radius from the focal points along the line of transects were counted and identified using Birds of Western Africa field guide. In addition, plotless sampling technique was used in tree survey and identification was aided using the Flora of West Tropical Africa field guide. Data were analyzed in R Statistical Package. We recorded 5,359 and 627 individual birds and trees made up of 32 and 27 species belonging to 23 and 19 families respectively. H′bird, E′bird were not statistically different from H′tree, E′tree at p>0.05. The calculated Margalef species richness index D′tree = 4.04 while D′bird = 3.61, this also was not different statically. Influence of population sizes of sampled organisms on density was significantly different p=1.23 ×10-4. Environmental degradation is not only a critical issue for the birds and plants but could have detrimental impacts on humanity as our future well-being is dependent on maintaining the biodiversity around us.
Keywords: Bird; Diversity; Evenness; Government College Kaduna; Richness; Tree